Regulator of G-Protein Signaling 2 Repression Exacerbates Airway Hyper-Responsiveness and Remodeling in Asthma - Jiang, Haihong (Am J Respir Cell Mol Biol, 2015)
G protein–coupled receptors (GPCRs) are important regulators of cell functions in asthma. We recently reported that regulator of G-protein signaling (RGS) 2, a selective modulator of G(q)-coupled GPCRs, is a key regulator of airway hyper-responsiveness (AHR), the pathophysiologic hallmark of asthma. Because RGS2 protein levels in airway cells were significantly lower in patients with asthma compared with patients without asthma, we further investigated the potential pathological importance of RGS2 repression in asthma. The human RGS2 gene maps to chromosome 1q31. We first screened patients with asthma for RGS2 gene promoter single-nucleotide polymorphisms (SNPs) and found significant differences in the distribution of two RGS2 SNPs (A638G, rs2746071 and C395G, rs2746072) between patients with asthma and nonasthmatic subjects. These two SNPs are always associated with each other and have the same higher prevalence in patients with asthma (65%) as compared with nonasthmatic subjects (35%). Point mutations corresponding to these SNPs decrease RGS2 promoter activity by 44%. The importance of RGS2 down-regulation was then determined in an acute IL-13 mouse model of asthma. Intranasal administration of IL-13 in mice also decreased RGS2 expression in lungs by ∼50% and caused AHR. Although naive RGS2 knockout (KO) mice exhibit spontaneous AHR, acute IL-13 exposure further increased AHR in RGS2 KO mice. Loss of RGS2 also significantly enhanced IL-13–induced mouse airway remodeling, including peribronchial smooth muscle thickening and fibrosis, without effects on goblet cell hyperplasia or airway inflammation in mice. Thus, genetic variations and increased inflammatory cytokines can lead to RGS2 repression, which exacerbates AHR and airway remodeling in asthma.